Morphological characteristics and variability of traditional starch forming coix (Coix lacryma-jobi var. ma-yuen) populations from Mindanao Island, Philippines - SANCHO G. BON; GERLIE P. ANTESCO; ELMER E. ENICOLA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Bon SG, Antesco GP, Enicola EE. 2023. Morphological characteristics and variability of traditional starch forming coix (Coix lacryma-jobi var. ma-yuen populations from Mindanao Island, Philippines. Biodiversitas 24: 4382-4391. Adlay (Coix lacryma-jobi var. ma-yuen (Rom.Caill.) Stapf) is an underutilized crop in the Philippines with high potential. Characterization and elucidation of the available variability among the local adlay populations are essential information for its improvement and better utilization. The study aimed to characterize the qualitative morphological traits of 34 traditional adlay populations from Mindanao Provinces and assess diversity by the Shannon Index and similarity by multivariate clustering. Results showed that all populations shared the same morphotypes in five descriptors but were variable for the rest. Six populations showed intense leaf anthocyanin coloration, and 23 expressed upright growth habits. Three types of leaf blade colors were observed, while the intensity of anthocyanin coloration of culms was expressed in four types. Most populations had semi-pubescent or highly pubescent leaves, generally intermediate leaf orientation and non-glaucous leaves. Immature grains were generally light green but expressed four color types at maturity, mostly circular with furrows on the surface. Diversity Indices (H') ranged from low to high. Leaf blade pubescence, anthocyanin coloration of culm, and mature grain color had high H' values. Cluster analysis showed that the variability was narrow, where overall clustering achieved 0.50 similarity. At 0.65 similarity, three groups can be derived with three populations as outliers. Clustering can be attributed to the differences in seedling color, anthocyanin coloration, plant growth habit, immature grain color, mature grain color, and shape. The study established the morphological description of the qualitative traits of traditional Philippine adlay and assessed diversity to be generally intermediate, where populations can be clustered into subgroups according to the degree of morphotype similarities. Clustering, however, was not related to provenances. It is recommended to conduct further geographic germplasm sampling, marker-based characterization, and agronomic evaluation to dissect further the genetic diversity and crop potential of the local adlay populations.